Efficacy and safety of postoperative dexmedetomidine sedation following coronary surgery - Borkowski, Jarosław; Knapik, Piotr; Czapla, Jerzy; Nadziakiewicz, Paweł; Borowik, Dawid (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Background : Dexmedetomidine is a highly selective α2 adrenoreceptor agonist with sedative properties. Aim: To compare efficacy and safety of postoperative sedation with dexmedetomidine and midazolam. Material and methods : A prospective randomized trial was performed in 58 patients undergoing coronary surgery. Patients in group I (n = 26) were sedated with a loading dose of 0.25 µg kg-1 dexmedetomidine followed by a continuous infusion of 0.1 µg kg-1 h-1 and interventional additional injections of midazolam, while patients in group II (n = 32) were sedated with interventional injections of midazolam only. The dosing of dexmedetomidine was initially twice as high, but it was reduced by 50% after two serious side effects occurred. Parameters of the postoperative course were compared between the groups. P < 0.05 was considered significant. Results : Two serious side effects (acute, reversible heart failure) were noted following the administration of a higher dose of dexmedetomidine. The study was stopped and a new revised protocol was proposed to the Ethical Committee for consideration. After the approval, the study was continued according to the new protocol. Comparable and satisfactory parameters of sedation were achieved in both study groups, however the postoperative course including awakening and extubation time was fully comparable in both groups. Doses of drugs used in a postoperative period were also comparable. In patients who underwent dexmedetomidine sedation, significantly higher volumes of colloid solutions were used to provide normal values of arterial pressure. Conclusions : Sedation with the use of dexmedetomidine in the standard dose is not safe in patients with a low postoperative risk. Sedation with a reduced dose of dexmedetomidine in this group of patients is safe, but not effective if started after admission to the postoperative care unit.